Retratos imaginários: fotografia, tempo livre e indústria cultural - Gelka Arruda de Barros (2013)
This dissertation is an investigation into the relationship between man and the image in contemporaneousness, permeated by photography and the culture industry. Based on the philosophical musings of Critical Theory and Vilém Flusser, along with other theorists of the image, the paper presents considerations regarding the process of construction of subjectivity, trying to establish the relationship of the subject with his own image in contemporary society. Therefore, illustrates the occasional moments of the development process of optical mechanisms that enabled the advent of photography aswe know it in the current patterns and their implications for our ways of seeing. In order to widen the debate on the theme, interviews were conducted from photographs chosen by respondents, hoping to collect the production of the senses of the social individual, enabling a deeper dialogue with the theoretical references adopted. This approach allowed the tensions between the individuals and the image to be established in their ways of apprehending the world and to represent themselves to the world.